OPTIMALISASI LAYANAN LAUNDRY SEBAGAI PENDUKUNG MANAJEMEN PENDIDIKAN: Studi kasus Di Pondok Pesantren Islamic Centre Bin Baz Yogyakarta - Sari Anggreini; Khairil Hafiz; Eko Ngabdul Shodikin (BAMALA Institute, 2024)
This research aims to determine the contribution of laundry services to education at the Islamic Centre Bin Baz Islamic boarding school. Using a descriptive qualitative method, data was collected through observations and interviews with students and the laundry supervisor. The observation results of the students revealed several issues, such as poor washing quality, frequent clothing mix-ups, long washing times, and limited capacity. The interview results with the laundry supervisor, Mrs. Fita, indicated that improvements had been made, such as changes in location and facility upgrades. The research findings state that: (1) The laundry service at the Islamic Centre Bin Baz Islamic boarding school is running well and effectively. However, there is a lack of communication to parents regarding the new location of the boys' laundry. (2) The Islamic Centre Bin Baz Islamic boarding school always strives to improve the quality of various facilities, including the laundry service. Data analysis shows that the laundry management is running well and effectively, continuously seeking improvements to enhance the students' comfort and focus on learning. Recommendations are provided to enhance service quality, including maintenance of washing machines, increasing load capacity, and adjusting clothing collection schedules. Continuous evaluation and monitoring are recommended for implementing recommendations and sustaining improvements in laundry management. In previous research, the focus was on how laundry services could reduce the administrative and operational burdens of educational institutions, and all students were already using the institution's laundry services properly. In this study, the author delves deeper into how laundry services contribute to educational management? and aims to ensure that students can use the laundry services comprehensively? and how these services have a positive impact on educational management?. It is hoped that this research will provide a positive contribution to the development of educational management at the Islamic Centre Bin Baz Islamic boarding school and supporting services such as laundry.